Are post-communist interest organizations learning to lobby? Exploring the "coming-of-age" of Central and Eastern European interest groups. Issue 7 (3rd October 2022) - Dobbins, Michael; Horváth, Brigitte; Labanino, Rafael Pablo
ABSTRACT: Countless scholars have explored the emergence, stability and transformation of interest intermediation structures in western democracies and beyond [Jahn, "Changing of the Guard"; Schmitter, "Corporatism is Dead!"; Siaroff, "Corporatism in 24 Industrial Democracies".]. In this article we take a new avenue by exploring the "micro-level" impact of (quasi-)representation monopolies and high or low access on organized interests, namely at the level of groups themselves. Looking at Central and Eastern European organizations, we assess how the inclusion within or exclusion from frequent interactions with the state impacts the internal development of organized interests? Do excluded groups seek to professionalize their operations to increase their chances of eventually accessing policy-makers? Do they expand ties with other groups to increase their joint political clout? Or do they flee the national political arena and focus more on regional- or European-level activities? Based on a survey of Central and Eastern European organized interests, the analysis reveals that political inclusion indeed strongly enhances organizational development and intergroup cooperation. Yet, we also show that even occasional political participation boosts the lobbying capacities of organizations, in particular younger, mainly civic organizations. Altogether, the data shed positive light on the responsiveness of interest organizations operating in a region previously often overlooked in interest group research.